Unilateral biportal endoscopic lumbar interbody fusion enhanced the recovery of patients with the lumbar degenerative disease compared with the conventional posterior procedures: A systematic review and meta-analysis - Yang, Honghao; Cheng, Fengqi; Hai, Yong; Liu, Yuzeng; Pan, Aixing (Frontiers in Neurology, 2023)
Background Minimally invasive endoscopic technique is an important component of Enhanced Recovery After Surgery (ERAS) protocol for neurosurgery. In recent years, unilateral biportal endoscopic lumbar interbody fusion (ULIF) has been used in the treatment of lumbar degenerative diseases (LDD). This study aims to investigate whether ULIF could enhance the recovery of patients with LDD compared with the conventional minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) or posterior lumbar interbody fusion (PLIF). Methods A comprehensive literature search was performed for relevant studies in PubMed, EMBASE, Web of Science, Cochrane Library database, China National Knowledge Internet, and Wanfang database. Surgical data, clinical outcomes, radiographic outcomes, and surgical complications were compared between patients with LDD who underwent ULIF and those who underwent conventional MI-TLIF or PLIF. Results Notably, 12 studies, comprising 981 patients with LDD, were included. Of these patients, 449 underwent ULIF and 532 patients (355 MI-TLIF and 177 PLIF) were treated with conventional procedures. There was no significant difference in the fusion rate, cage subsidence rate, and surgical complications between the ULIF group and the MI-TLIF or PLIF group. Compared with MI-TLIF, the ULIF group presented a significantly reduced estimated blood loss (EBL) (WMD, −106.00; 95% CI −140.99 to −71.10, P < 0.001) and shorter length of hospital stay (LOS) (WMD, −1.27; 95% CI −1.88 to −0.66, P < 0.001); better short-term improvement in ODI (WMD, −2.12; 95% CI −3.53 to −0.72, P = 0.003) and VAS score for back pain (VAS-BP) (WMD, −0.86; 95% CI −1.15 to −0.58, P < 0.001) at 1 month post-operatively. Compared with PLIF, the ULIF group presented a significantly reduced EBL (WMD, −149.22; 95% CI −284.98 to −13.47, P = 0.031) and shorter LOS (WMD, −4.40; 95% CI −8.04 to −0.75, P = 0.018); better short-term improvement in VAS-BP (WMD, −1.07; 95% CI −1.77 to −0.38, P = 0.002) and VAS score for leg pain (VAS-LP) (WMD, −0.40; 95% CI −0.72 to −0.08, P = 0.014) at 1–2 week post-operatively; enhanced short- and long-term improvement in ODI at 1 month post-operatively (WMD, −3.12; 95% CI −5.72 to −0.53, P = 0.018) and the final follow-up (WMD, −1.97; 95% CI −3.32 to −0.62, P = 0.004), respectively. Conclusion Compared with conventional MI-TLIF and PLIF, ULIF was associated with reduced EBL, shorter LOS, and comparable fusion rate as well as complication management. Compared with MI-TLIF, a better short-term improvement in VAS-BP and ODI was achieved by ULIF; compared with open PLIF, additional enhanced short-term improvement in VAS-LP and long-term improvement in ODI were observed in ULIF. ULIF could enhance the recovery of patients with LDD compared with conventional posterior procedures. Systematic trial registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=230695, CRD42021230695.